The YellowPress Periodical : #3. - Gorus, Kim; Crombez, Thomas; Heirwegh, Ward; LAke, Yvonne; Morris, Wendy; Onghena, An; Van Beirendonck, Michel; Van Dijk, Hanne; Van Gansen, Kristof; Van Haute, Katrien; Van Rijn, Ilse (Antwerpen : KdG / Sint Lucas Antwerpen)
An Onghena & Hanne Van Dyck: Blacking Out on Black Holes ; Ilse Van Rijn: Writing Wanderlines ; Yvonne Lake: The Uncanny Bard and the Freudian Robot ; Thomas Crombez (ed.): Over the Serif ; Wendy Morris: Off by Heart and Out of Breath. A Wandergram for a Lecture
boek